(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
The greater Mymensingh district of Bangladesh, particularly the hilly areas are rich in Bryophyte flora. The present paper on class Hepaticopsida (Liverworts) and Anthocerotopsida (Hornworts) represents primary as well as secondary data collection and includes an account of 48 species under 12 genera, nine families and four orders. An alphabetic arrangement of taxa with short description, habitats, localities, names of collectors with dates and collection numbers are provided. Keywords: Bryophytes; Hepaticopsida; Anthocerotopsida; Liverworts; Hornworts; Mymensingh District. DOI: 10.3329/bjpt.v17i1.5390 Bangladesh J. Plant Taxon. 17(1): 55-67, 2010 (June)